A metabolomics study: CdTe/ZnS quantum dots induce polarization in mice microglia. (May 2020) - He, Keyu; Liang, Xue; Wei, Tingting; Liu, Na; Wang, Yan; Zou, Linyue; Bai, Changcun; Yao, Ying; Wu, Tianshu; Kong, Lu; Zhang, Ting; Xue, Yuying; et al.
Abstract: In this study, a metabolomic analysis was used to reveal the neurotoxicity of the CdTe/ZnS QDs via microglia polarization. A gas chromatography-mass spectrometer (GC-MS) was applied to uncover the metabonomic changes in microglia (BV-2 cell line) after exposure to 1.25 μM CdTe/ZnS QDs. 11 annotated metabolic pathways (KEGG database) were significantly changed in all exposed groups (3 h, 6 h, 12 h), 3 of them were related to glucose metabolism. The results of the Seahorse XFe96 Analyzer indicated that the CdTe/ZnS QDs increased the glycolysis level of microglia by 86% and inhibited the aerobic respiration level by 54% in a non-hypoxic environment. In vivo study, 3 h after the injection of CdTe/ZnS QDs (2.5 mM) through the tail vein in mice, the concentration of the CdTe/ZnS QDs in hippocampus reached the peak (1.25 μM). The polarization level of microglia (Iba-1 immunofluorescence) increased 2.7 times. In vitro study, the levels of the extracellular TNF-α, IL-1β and NO of BV-2 cells were all increased significantly after a 6 h or 12 h exposure. According to the results of the Cell Counting Kit-8, after a 6 h or 12 h exposure to the CdTe/ZnS QDs, the exposed microglia could significantly decrease the number of neurons (HT-22 cell line). This study proved that CdTe/ZnS QDs could polarize microglia in the brain and cause secondary inflammatory damage to neurons. There are potential risks in the application of the CdTe/ZnS QDs in brain tissue imaging. Graphical abstract: Image 1 Highlights: CdTe/ZnS QDs could enter into the mouse brain through tail vein injection. CdTe/ZnS QDs could inhibit aerobic respiration in microglia after exposure. We first found that CdTe/ZnS QDs could polarize the microglia. CdTe/ZnS QDs could induce inflammatory damage to the neurons. The inflammatory damage is dependent on the cytotoxicity of the CdTe/ZnS QDs.